Propuesta de estudio de tiempos y movimientos para la estandarizanción de métodos en el área de producción de la empresa “CASA MUEBLES RIVERA” ubicada en el Valle del Cauca. - Pesillo Montilla, Angie Vanessa (Universidad Antonio Nariño, 2022)
The study of times and movements is a methodology used to know, identify and analyze the processes for activities to generate delays, bottlenecks or downtime that the production process in a company and according to the data obtained, they can be reduced or eliminated to give solution to these shortcomings and thus optimize times and movements in each work area.